MURABAHA FINANCING DURING THE COVID 19 PANDEMIC: STUDY CASE SHARIA COMPLIANCE IN BPRS DANA AMANAH SURAKARTA YEAR 2019-2021 عقد المرابحة في جائحة وباء كوفيد: دراسة تطبيقية في البنوك الشريعة بسوركرتا - Aisyah Nurhayati; Moh. Abdul Kholiq Hasan; Imron Rosyadi; Aisha Bahaaeldin Eprahim Ali (Profetika: Jurnal Studi Islam, 2022)
The purpose of this study is to examine sharia compliance in the implementation of murabaha contracts at BPRS Dana Amanah Surakarta during the pandemic covid-19. This research is field research with an interpretive approach. Data analysis in this study uses content analysis which analyzes the main sources of research in the form of interview data and contracts documents related to murabaha at BPRS Dana Amanah Surakarta and second sources. The conclusion is that there are two murabaha contracts, namely the murabahah lil wa'ad bi syira contract and the murabahah bil wakalah contract. In the Murabaha bil wakalah contract, there are two schemes, the first is direct payment to the supplier and the second is payment through the customer's account. The implementation of the murabahah contract at the Surakarta Amanah Fund BPRS is per sharia and DSN-MUI fatwa, there is only a slight difference in the application of the second scheme of murabahah bil wakalah with the DSN-MUI fatwa.الملخص:تهدف الدراسة معرفة مدى الإلتزام بالشريعة في تنفيذ عقود المرابحة وتأثير الوباء على عقود المرابحة في BPRS Dana Amanah Surakarta. هذا البحث هو بحث كيفي ميداني. تستخدم طريقة تحليل المحتوى لتحليل البيانات الرئيسية والثانوية من المقابلة ووثائق العقد المتعلقة بالمرابحة في  BPRS Dana Amanah Surakarta والمجلات المحكمة وغيرها. وتظهر نتائج البحث:أن هناك نوعين من عقود المرابحة، وهما عقد المرابحة بالوعد للشراء وعقد المرابحة بالوكالة. يوجد في عقد المرابحة بالوكالة طريقتان، الأول هو الدفع المباشر للمورد والثاني هو الدفع من خلال حساب العميل. وتطبيق عقد المرابحة  قد توافق مع الشريعة وفتوى DSN-MUI، لا يوجد سوى اختلاف قليل في تطبيق المخطط الثاني للمرابحة بالوكالة مع فتوى DSN-MUI. طرأ تغير على توجهات عقود المرابحة خلال الجائحة، وتحديدا من التمويل الفردي إلى التمويل المجمع، وانخفاض في عدد عقود المرابحة من 2019-2021.